PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT PANCA GARDA ULTIMA JAKARTA BARAT - Cici Mawati Simamora; Syawaludin (Journal of Research and Publication Innovation, 2025)
The research aims to find out the impact of work motivation and work discipline on the performance of employees of PT  Panca Garda Ultima West Jakarta. The kind of research used in this research is quantitative research. Data analysis techniques used are validity tests, reliability tests, classical assumption tests consisting of normality tests,  ulticollinearity tests and heterocadasthesis tests, double linear regression tests, correlation coefficients, determination cofficients and hypothetical tests that consist of partial t tests and simultaneous f tests. Thus, the results of the study based on the test t on the work motivation variable thitung 2,478 > ttable 1,997 with a significant rate of 0,000 < 0,05, means that the job motivation (X₁) has an influence on the performance of employees (Y) and the work discipline variable (X₂) has a calculation of 6,326 > tables 1,997, meaning that the working discipline (X₂) has an impact on employee performance (Y). whereas the result of the test F is obtained that the value of the calculation 63,729 > ftable 3,13 has a significant level of 0.000< 0,05. Work motivation and labour discipline against employee behavior regression Y = 1,621 + 0,260X₁ + 0,618X₂ The correlation value I is 0.685. With a determination coefficient of 65,5% while the remaining (100-65,5%) = 34.5% is influenced by other factors.